SOSIALISASI HAK KEKAYAAN INTELEKTUAL BAGI PELAKU UMKM DI DESA ABUAN, BANGLI - I Kadek Alit Ambara Wijaya; Ida Bagus Gede Indramanik; I Made Sumartana; I Made Kartika; I Dewa Gede Putra Sedana; Bayu Mahaputra (Media Bina Ilmiah, 2024)
Intellectual property rights hereinafter referred to as IPR are rights that arise as an effort to protect the law of a property born from the results of human intellectual abilities. The purpose of IPR is to protect the work that has been made by humans to get juridical protection. MSME actors in Abuan Village do not yet know how important IPR is in running MSMEs. The solution provided regarding this matter is the provision of legal socialization about IPR so that MSME actors in Abuan Village know how important IPR is in their MSMEs. This socialization mechanism was carried out at the Abuan Village office by inviting resource persons and bringing MSME actors in Abuan Village to be given socialization related to IPR. As a result of this socialization, MSME actors in Abuan Village know the importance of registering their work to obtain copyright as well as details of the costs incurred and procedures for registration